Excess warming of a Central European lake driven by solar brightening. Issue 10 (19th October 2016) - Schmid, M.; Köster, O.
Abstract: Recent trends in summer surface temperatures of many lakes exceed the corresponding air temperature trends. This disagrees with expectations from lake surface heat budgets, which predict that lake surface temperatures should increase by 75–90% of the increase in air temperatures. Here we investigate the causes for this excess warming for Lower Lake Zurich, a representative deep and stratified Central European lake, by a combined data analysis and modeling approach. Lake temperatures are simulated using a one‐dimensional vertical model driven by 33 years of homogenized meteorological data. The model is calibrated and validated using an equally long time series of monthly water temperature profiles. The effects of individual forcing parameters are investigated by scenarios where the trends of single variables are retained while those of all other forcing variables are removed. The results show that ∼60% of the observed warming of spring and summer lake surface temperatures were caused by increased air temperature and ∼40% by increased solar radiation. The effects of the trends of all other forcing variables were small. Following projections of climate models, the increasing trends in solar radiation, and consequently the excess warming of lake surface temperatures, are not likely to continue in the future. Key Points: Surface temperature trends of Lake Zurich are larger than expected from air temperature trends Most of this excess warming was caused by solar brightening We do not expect the excess warming to continue into the future